A rare case of intralobar pulmonary sequestration: combined endovascular and video-assisted thoracoscopic approach - Fabbri, Nicolò (AME Case Rep, 2018)
Pulmonary sequestration is a congenital malformation characterized by cystic, non-functioning embryonic lung tissue supplied by an abnormal systemic artery. It’s a rare disease widely variable in clinical presentation and severity, depending mostly on the degree of lung involvement and location in the thoracic cavity. Most patients have recurrent infections and inflammatory conditions in the affected lobe. Surgical resection continues to be the gold standard of therapy and in this context anatomical resection is the procedure of choice and yields excellent long-term results. There are few studies reporting the use of combined endovascular and thoracoscopic approaches for pulmonary sequestration. We describe a case of intralobar pulmonary sequestration located in the lower lobe of the right lung, which was treated with video-assisted thoracoscopic surgery (VATS) after endovascular embolization of systemic artery arising from celiac trunk.